ЎҚИТУВЧИНИНГ ИЖОДИЙ ПЕДАГОГИК МАҲОРАТИ ВА ХУСУСИЯТИ - Романова, С.; Койшыбаева, Г. (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of the teacher’s creative approach that is reflected at different stages of the development of pedagogical activity independence, flexibility and progress of the teacher’s thinking.
Keywords: creative; pedagogical activity; pedagogical circumstances; possibility; manager